2024
DOI: 10.1186/s12967-024-05069-y
|View full text |Cite
|
Sign up to set email alerts
|

HBV DNA polymerase upregulates the transcription of PD-L1 and suppresses T cell activity in hepatocellular carcinoma

Yan Jia,
Jianing Zhao,
Chunqing Wang
et al.

Abstract: Background In HBV-associated HCC, T cells often exhibit a state of functional exhaustion, which prevents the immune response from rejecting the tumor and allows HCC to progress. Moreover, polymerase-specific T cells exhibit more severe T-cell exhaustion compared to core-specific T cells. However, whether HBV DNA polymerase drives HBV-specific CD8+ T cell exhaustion in HBV-related HCC remains unclear. Methods We constructed a Huh7 cell line stably e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…The surface expression of PD-1 on Jurak cells and T cells serves as a marker for both exhaustion and over-activation, as demonstrated in previous studies 69 , 70 . Another study has shown that PHA and IL2 have a stimulatory effect on PD1 expression at the protein level in Jurak cells 71 .…”
Section: Discussionsupporting
confidence: 62%
“…The surface expression of PD-1 on Jurak cells and T cells serves as a marker for both exhaustion and over-activation, as demonstrated in previous studies 69 , 70 . Another study has shown that PHA and IL2 have a stimulatory effect on PD1 expression at the protein level in Jurak cells 71 .…”
Section: Discussionsupporting
confidence: 62%